Isothermal amplification of DNA using quadruplex primers with fluorescent pteridine base analogue 3‐methyl isoxanthopterin. Issue 6 (June 2014) - Gogichaishvili, Shota; Johnson, John; Gvarjaladze, David; Lomidze, Levan; Kankia, Besik
ABSTRACT We previously developed a method, known as quadruplex priming amplification (QPA), which greatly simplifies DNA amplification and quantification assays. QPA employs specific primers based on GGGTGGGTGGGTGGG (G3T) sequence, which upon polymerase elongation spontaneously dissociates from the target and folds into a stable quadruplex. Fluorescent nucleotide analogs, when incorporated into these primers, emit light upon quadruplex formation and permit simple, specific, and sensitive quantification without the attachment of probe molecules. Here, we studied optical [fluorescence and circular dichroism (CD)] and thermodynamic properties of the G3T sequence and variants incorporating 3‐methylisoxanthopterin (3MI), a highly fluorescent nucleotide analog suitable for QPA. CD studies demonstrate that the incorporation of 3MI does not change the overall tertiary structure of G3T; however, thermal unfolding experiments revealed that it significantly destabilizes the quadruplex. Enzymatic studies revealed that Taq and Bst are practically unable to incorporate any nucleotides opposite to template 3MI. Based on this knowledge, we designed QPA assays with truncated targets that demonstrate efficient amplification around 55°C. Overall, these studies suggest that 3MI‐based QPA is a useful assay for DNA amplification and detection. © 2013 Wiley Periodicals, Inc. Biopolymers 101: 583–590, 2014.